MINDFULNESS AND FIVE FACTOR PERSONALITY TRAITS AS PREDICTORS OF HUMOR - Ozyesil, Zumra; Deniz, M. Engin; Kesici, Sahin (SLOVAK ACAD SCIENCES INST EXPERIMENTAL PSYCHOLOGY, 2013)
The study aims to determine if mindfulness and the Five Factor Personality Traits significantly predict humor styles. The participants of the study were a total of 502 undergraduate students, 300 (59.8%) female and 202 (40.2%) male. Humor Styles Questionnaire (HSQ), Adjective Based Personality Test (ABPT) and The Mindful Attention Awareness Scale (MAAS) were used in order to collect the data of the study. Pearson's Product Moments correlation technique and multiple regression analysis were employed for statistical analysis. The findings of the study show that mindfulness and the Five Factor Personality Traits significantly predict the subdimensions of humor styles.
Keywords: mindfulness; personality; humor styles; INDIVIDUAL-DIFFERENCES; ATTACHMENT STYLES; HEALTH; CONFLICT; SENSE; BIG-5; Psychology